PENGARUH KOMPETENSI, INDEPENDENSI, DUKUNGAN MANAJEMEN DAN KEAHLIAN PROFESIONAL TERHADAP EFEKTIVITAS AUDIT INTERNAL - Tria Warastuti; Yuneita Anisma; Devi Safitri (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2021)
This study aims to examine how competence, independence, management support and professional expertise affect the effectiveness of internal audit at universities in Pekanbaru City. The populations in this study were internal auditors in universities in Pekanbaru City. The sample in this study was selected using purposive sampling method. Based on the purposive sampling method, a sample of 18 universities was obtained with 65 internal auditors. This study uses primary data by distributing questionnaires online due to the COVID-19 pandemic. The analytical method used in this study uses the Structural Equation Model method based on Partial Least Square (PLS) with the help of Smart PLS 3.The results of this study indicate that: (1) Independence has a significant positive effect on the effectiveness of internal audit with a t value of 3,440>1,96 and the results of P-Value 0.001 which is less than 0.05, (2) Management support has a significant positive effect on the effectiveness of internal audit with a t value of 4.185>1.96 and a P-Value of 0.000 which is less than 0,05. Meanwhile, Competence and Professional Proficiency do not significantly influence the effectiveness of internal audit